Respiratory disturbances and high risk of sudden death in the neonatal connexin‐36 knockout mouse - Leonel F. Pérez‐Atencio; Ana M. Casarrubios; José M. Ibarz; Juan A. Barios; Cristina Medrano; David Pestaña; David L. Paul; Luis C. Barrio (Physiological Reports, 2021)
Abstract Neural circuits at the brainstem involved in the central generation of the motor patterns of respiration and cardiorespiratory chemoreflexes organize as cell assemblies connected by chemical and electrical synapses. However, the role played by the electrical connectivity mainly mediated by connexin36 (Cx36), which expression reaches peak value during the postnatal period, is still unknown. To address this issue, we analyzed here the respiratory phenotype of a mouse strain devoid constitutively of Cx36 at P14. Male Cx36‐knockout mice at rest showed respiratory instability of variable degree, including a periodic Cheyne–Stokes breathing. Moreover, mice lacking Cx36 exhibited exacerbated chemoreflexes to normoxic and hypoxic hypercapnia characterized by a stronger inspiratory/expiratory coupling due to an increased sensitivity to CO2. Deletion of Cx36 also impaired the generation of the recurrent episodes of transient bradycardia (ETBs) evoked during hypercapnic chemoreflexes; these EBTs constituted a powerful mechanism of cardiorespiratory coupling capable of improving alveolar gaseous exchange under hypoxic hypercapnia conditions. Approximately half of the homo‐ and heterozygous Cx36KO, but none WT, mice succumbed by respiratory arrest when submitted to hypoxia‐hypercapnia, the principal exogenous stressor causing sudden infant death syndrome (SIDS). The early suppression of EBTs, which worsened arterial O2 saturation, and the generation of a paroxysmal generalized clonic‐tonic activity, which provoked the transition from eupneic to gasping respiration, were the critical events causing sudden death in the Cx36KO mice. These results indicate that Cx36 expression plays a pivotal role in respiratory control, cardiorespiratory coordination, and protection against SIDS at the postnatal period.